2009
DOI: 10.1002/syn.20616
|View full text |Cite
|
Sign up to set email alerts
|

Human evidence of a supra‐spinal modulating role of dopamine on pain perception

Abstract: Although there is growing evidence supporting a role of dopamine in pain perception, the mechanisms by which dopamine influences pain processing remains to be determined. On the basis of preliminary findings, we put forth the hypothesis that dopamine is involved in endogenous pain modulation systems, and further discuss the implications of this hypothesis for the understanding of the physiopathology of chronic pain disorders associated with dysfunctional endogenous pain modulation systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 101 publications
2
72
0
3
Order By: Relevance
“…Human studies confirm that patients with fibromyalgia have lowered levels of monoamines (12) in their cerebrospinal fluid and higher levels of substance P (13) and nerve growth factor (14). Serotonin and norepinephrine are thought to be the key neurotransmitters in the descending pain inhibitory system, and dopamine also appears to be involved in pain control in the central nervous system (15,16). Altered serotonin metabolism associated with reduced transcription activity of the short allele of the serotonin transporter gene promoter occurs more frequently in patients with fibromyalgia than in healthy control subjects and has been linked to higher levels of depression and psychological distress (17).…”
mentioning
confidence: 99%
“…Human studies confirm that patients with fibromyalgia have lowered levels of monoamines (12) in their cerebrospinal fluid and higher levels of substance P (13) and nerve growth factor (14). Serotonin and norepinephrine are thought to be the key neurotransmitters in the descending pain inhibitory system, and dopamine also appears to be involved in pain control in the central nervous system (15,16). Altered serotonin metabolism associated with reduced transcription activity of the short allele of the serotonin transporter gene promoter occurs more frequently in patients with fibromyalgia than in healthy control subjects and has been linked to higher levels of depression and psychological distress (17).…”
mentioning
confidence: 99%
“…Although highly speculative, we consider dopamine signaling as a potential candidate able to preserve hedonic processing in the absence of opioid mediation. Along this line of reasoning, a recent review of the literature has shown a key role of dopamine on pain perception in humans, suggesting its involvement in endogenous pain modulation systems (Potvin et al, 2009). In addition, pleasure and reward expectation have been associated with increased phasic dopamine signaling (Schultz, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, some experimental studies have shown the opposite effect, where there appears to be a higher pain threshold and tolerance level in individuals with anxiety disorders or chronic pain [ 33 ]. This may be related to malfunctioning of the endogenous opioid system [ 114 ]. It has been suggested that this is related to the symptoms of emotional numbing present in PTSD, although the relationship between PTSD and chronic pain still remains unclear [ 48 ].…”
Section: Shared Vulnerability Modelmentioning
confidence: 96%